Factors Related to the Implementation of the Safety Management System and Occupational Health in the Inpatient Room Sultan Abdul Regional General Hospital Aziz Shah East Aceh Regency in 2022 - Afnina Afnina; Elvina Sari; Putri Indah Anisa; Nada Salsabila; Linda Jurwita; Andriani Mei Astuti (Journal of Social Research, 2022)
The Occupational Safety and Health Management System (SMK3) is a factor that plays an important role in hospital services. The purpose of this study was to determine the factors related to the implementation of SMK3 in the Inpatient Room of Sultan Abdul Aziz Syah Hospital, East Aceh Regency. The variables of this study are independent and dependent variables, where independent variables consist of knowledge, work environment, K3RS commitment, and K3RS supervision as well as dependent variables, namely the implementation of SMK3. The study was quantitative and cross-sectional with a population of 139 nurses and a large sample of 58 nurses taken by stratified random sampling technique. The data processed is in the form of primary data using questionnaires that are shared with nurses. Statistical tests were carried out using chi-square to find out the relationship between independent and dependent variables. The results of statistical tests with a significance level of 5% (? = 0.05) showed that there was a meaningful relationship between the variables of knowledge, work environment, the commitment of K3RS, and K3RS supervision with the variables of SMK3 implementation with a p-value obtained from each variable < 0.05. The implementation of SMK3 at the Sultan Abdul Aziz Shah Regional Hospital, East Aceh Regency, was included in the bad category of 27.6%. This shows that the implementation of SMK3 in the hospital has not been carried out properly. From the questions asked to nurses through questionnaires, there are several questions where the average nurse gives the lowest score on the questions for implementing SMK3, including in the use of PPE, attending seminars/training in the field of K3, attending K3 training, health checks, checking work environment conditions and supervising work environment conditions.